1976
DOI: 10.1073/pnas.73.7.2266
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of histone onto the replicating chromosome: newly synthesized histone is not found near the replication fork.

Abstract: Communicated by David M. Prescott, April 19,1976 ABSRACr We have studied the site of deposition of newly synthesized histone. It appears to be randomly distributed over the chromosomal material and does not become associated specifically with immediately post-replicational DNA, nor is it deposited in discrete continuous regions distal to the sites of DNA synthesis. The newly synthesized DNA, however, rapidly acquires a complement of chromosomal proteins; presumably, preexisting histones must migrate to beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1978
1978
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Likewise, previous mapping identified serine 1 as the main phosphorylated residue on H4, and this site is most likely occupied in the 11,083-Da form. H4 acetylation at lysines 5 and 12 and phosphorylation of serine 1 have been suggested to be cytoplasmic events occurring on free histones (32)(33)(34)(35). However, our isolation procedure involves precipitation of DNA-associated proteins; therefore the phosphorylation and deacetylation events we observe occur on chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, previous mapping identified serine 1 as the main phosphorylated residue on H4, and this site is most likely occupied in the 11,083-Da form. H4 acetylation at lysines 5 and 12 and phosphorylation of serine 1 have been suggested to be cytoplasmic events occurring on free histones (32)(33)(34)(35). However, our isolation procedure involves precipitation of DNA-associated proteins; therefore the phosphorylation and deacetylation events we observe occur on chromatin.…”
Section: Discussionmentioning
confidence: 99%
“…The progression of the DNA replication machinery disrupts the nucleosome in front of the replication fork, which is then reassembled onto the newly synthesized DNA strands in a random manner (15,20). The remaining gaps are subsequently filled up with newly translated histone molecules, leading to a mosaic pattern of new and old histone octamers (2,21). This process is assisted by the action of nuclear chaperones, which bind to the histones before deposition (14,34).…”
mentioning
confidence: 99%
“…The newly deposited histones are more loosely associated with the DNA than the bulk histones and mature slowly into a more stable chromatin structure. Assembly is achieved via an ordered deposition of H3 and H4, followed by the binding of H2A/H2B dimers and finally the interaction of the linker histone H1 with the chromatin fiber (19)(20)(21)(22)49).Posttranslational modifications of histone molecules are generally considered to play an important role during the establishment and maintenance of chromatin structures. The combination of histone modifications has been proposed to constitute a "histone code" (23, 55), which is involved in the maintenance of epigenetic information.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MNase digestion of extracts of TSPy5 virusinfected Cos7 cells indicated that the TSPy5 genome was assembled into chromatin, and restriction enzyme analysis of TSPy5 minichromosomes revealed that the Py ori core region was occupied by nucleosomes (data not shown). To inhibit extensive DNA replication and SV40 virion assembly that might disrupt histone modifications caused by Gal4 fusion proteins expressed in the Cos7 cells (49), aphidicolin was added to the cells at 16 h after infection. To validate ChIP assays as a means to study TSPy5 chromatin acetylation, we analyzed whether TSA treatment of Cos7 cells infected with TSPy5 viruses changed the acetylation status of TSPy5 chromatin.…”
Section: Resultsmentioning
confidence: 99%